1996
DOI: 10.1002/(sici)1099-1069(199609)14:3<111::aid-hon575>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcome in Solitary Bone Plasmacytomata With Combined Therapy

Abstract: Solitary bone plasmacytoma (SBP) is a rare presentation of plasma cell dyscrasias. Radiotherapy has been considered the treatment of choice, however, most patients will develop multiple myeloma, 3 to 10 years after initial diagnosis and treatment. No innovations have been introduced in the treatment of SBP in the last 30 years. We began a prospective clinical trial to assess the efficacy and toxicity of adjuvant chemotherapy with low doses of melphalan and prednisone administered to patients with SBP after rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 0 publications
0
43
0
2
Order By: Relevance
“…There has been only one relevant prospective trial thus far, and it evaluated the benefit of chemo radiotherapy in 53 patients. Although the study included a limited number of patients, it concluded that combination therapy increased survival duration as well as remission [30]. Kumar et al presented in a series of 25 SBP patients that angiogenesis was highly associated with disease progression to myeloma [31].…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one relevant prospective trial thus far, and it evaluated the benefit of chemo radiotherapy in 53 patients. Although the study included a limited number of patients, it concluded that combination therapy increased survival duration as well as remission [30]. Kumar et al presented in a series of 25 SBP patients that angiogenesis was highly associated with disease progression to myeloma [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to the current guidelines, additional C/T is not generally recommended unless there is suboptimal response to R/T, relapse, or progression to MM . However, patients with large masses and high‐grade histology may have some benefit from the additional use of C/T, as supported in previous studies . In the past decade, there have been major advances in the treatment of MM.…”
Section: Introductionmentioning
confidence: 95%
“…The role of adjuvant chemotherapy (C/T) in the treatment of SP was explored in several published studies with inconclusive results . According to the current guidelines, additional C/T is not generally recommended unless there is suboptimal response to R/T, relapse, or progression to MM .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a decrease in the amount of beta-lymphocytes and the mean age of the patients is 60 years [1]. Plasmacytoma is a myelomatous mass that may be solitary, in combination with multiple myeloma or may progress to a generalized disease [7-9].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmacytomas are referred to benign lesions that may progress to multiple myeloma, a fatal neoplasm [1]. Skull plasmacytomas are unusual tumors accounting for 4% of all plasma cell tumors [1-6]. We report on a rare case of a skull plasmacytoma in a patient with active tuberculosis and no evidence of multiple myeloma that was successfully treated by surgery alone.…”
Section: Introductionmentioning
confidence: 99%